The Moisture Content Effect on Full Cell Process of Bamboo Preservation - Permadi, Pipin (1990)

(untitled)
The retention, penetration and also the distribution of CCA preservative in three different conditions (fresh, partially dry and dry) of bamboo of Gigantochloa scortechinii were studied. The study also were done in different portions (bottom and top) and different part of culms (inner and outer) of bamboo. Treating process applied was full cell process with one, two and three hours pressure period. The results indicated that Preservative retention were affected by moisture content and portions of the bamboo, while preservative penetration only affected by moisture content. The lower the moisture content the higher the retention and the deeper the penetration of preservative. Preservative solution enter the culms, besides from the axial directions also from inner to outer part of the culms. It makes the preservative retention in the\inner part of the culms were higher than in the outer part. Preservative penetration and retention in fresh bamboo, even though lower than dry and partially dry bamboo but can reach Malaysian Standard (MS.360:1986) for interior purposes. Moreover the dried bamboo, where the moisture content is below 15 % and part i ally dried bamboo, where the moisture content are between 40 to 50 % can reach Malaysian Standard for both interior and exterior purposes.